Implementation,Simulation of Four Switch Converter Permanent Magnet Brushless DC Motor Drive for Industrial Applications (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This Research paper proposes a low cost four switch three phase inverter (FSTPI) fed brushless DC (BLDC) motor drive for Active power factor correction for residential applicationswith out environmental issues. This proposed system is simplified the topological structure of the conventional six switch three phase inverter (SSTPI) and includes an active power factor correction in front end rectifier which results in sinusoidal input current and it closed to unity power factor. In this project a new structure of four switch three phase inverter with reduced number of switches for system is introduced. This system consists of single phase rectifier and four switch three phase inverter. This proposed inverter fed BLDC motor used in Sensorless control schemes. To improve sensorless control performance, six commutation modes based on direct current controlled PWM scheme is implemented to produced the desire Torque-Speed characteristics. This four switch three phase inverter is achieved by the reduction of switches, low cost control and saving of hall sensor. The design and implementation of low cost four switch inverter for Brushless motor drive with active power factor correction  have been conducted successfully and valediction  of the proposed sensorless control for four switch three phase inverter fed BLDC motor drive is developed and analysed using both  MATLAB/SIMULINK and hardware results  are verified out successfully.